Elongator: An Ancestral Complex Driving Transcription and Migration through Protein Acetylation. (12th January 2011) - Creppe, Catherine; Buschbeck, Marcus
Abstract : Elongator is an evolutionary highly conserved complex. At least two of its cellular functions rely on the intrinsic lysine acetyl-transferase activity of the Elongator complex. Its two known substrates—Histone H3 and α-Tubulin—reflect the different roles of Elongator in the cytosol and the nucleus. A picture seems to emerge in which nuclear Elongator could regulate the transcriptional elongation of a subset of stress-inducible genes through acetylation of Histone H3 in the promoter-distal gene body. In the cytosol, Elongator-mediated acetylation of α-Tubulin contributes to intracellular trafficking and cell migration. Defects in both functions of Elongator have been implicated in neurodegenerative disorders.